MICROCEPHALY BRAIN UNFINISHED (Fiep Bulletin - online, 2017)
This article is to demystify what has been written on this subject to date, about microcephaly. Come show the realcauses of this event through a new survey on mater contractile cells that is characterized by a set of highly specialized cells,organized, rational and accounting for all vital commands in our body, contractions, nerve synapses, reflex movements , systole,diastole, gas exchange, afferent and efferent systems, connective tissue etc. They are able to make an optical reading over tengenerations of cells around them, identifying their DNA.The CCMs appear to be five pairs of cells but are actually six pairs of cells, which sometimes JokeR and Beta are unitedin one block as in the cardiac system.The CCMs, representing the set of all our heredity (24 generations of maternal grandparents, 24 generations ofgrandparents) always appear in pairs and alternately. They are responsible for all our heredity, our DNA.Microcephaly is therefore an event resulting from invasive procedures to atrial cube six command pairs of cells, calledContractile Cells Mater Reverse, which happens fast closing of the brain cell also called command deoxyribose. That is becausethe MCCs that are control cells have a remarkable ability to make an optical other cells around them, or at a distance of up to tengenerations, and identify a JokeR-Delta brain is being formed, ie one brain contemplated by eight brains or parents and maternalgrandparents and paternal in pairs and alternately, starting with maternal grandparents and then grandparents, namely: Aa (Alfha-)father and mother-Bb (Beta ) the maternos- grandparents Cc (Ceci) grandparents paternos- Dd (Delta) maternal bizavós; so wehave a brilliant child." O c c u r r e n c e s o f m a l f o r m a t i o n i n i n f a n t s h a s b e e n a s s o c i a t e d w i t h Z i k a v i r u s . . . "(exame.abril.com.br/brasil/ferramentas zika virus and microcephaly)The researchers say that in early pregnancy, the virus can cause brain damage and interfere with brain developmentstages. In fact, those who cause these injuries are the Reverse command cells. According to researchers on the subject, thegreater risk of microcephaly by Zika virus still happens in cerebral cortex development phase of the fetus that is in the first fourmonths of pregnancy.In chromosomal split, we have the first 24 pairs of cells (the pair of No. 25 is deleted every intersection) scienceinterprets as 23 pairs of chromosomes only, is that JokeR, formed by the father and mother are in one block together, and this tape,we have the main tape command in the body which will be explained in front, they are;Aa Bb-Cc-Dd-Ee-Ff-Gg-Hh-Ii-Jj. In this tape, are reversed from Ee called Reverse And so then we have two cell groups,to consider a group of good cells, versus a group of cells reverse. The reversas- cells (DC- Ee - Gg- II) to detect the formation of thisbrain, you want possession of it at any cost, the deoxyribose cells (Aa Bb-Dd-Ff-Hh-Jj) conflicts with the reverse cell and these twocell groups waging a battle with big rivalry going on a general sweep in all the cells around them to ten generations (so they seek,following the generations that brain q is being formed for this reason they They are moving in several places where there can be arelationship of the brain) by the pursuit of JokeR-Delta brain, with the rapid closing of this by deoxyribose, thus getting theunfinished brain.On a brain, we can say that its size does not necessarily measures your ability, it can be small, and with all functionswithin the normal range, but will not be free of postnatal microcephaly and that a brain can be born unfinished and escape thenormal range and may be born small and grow, since he was born perfect and may be born large decrease, everything will goaccording to the movement of MCCs.(Https: en Wikipedia.org/wik/microcefalia.)"It is a neurological condition where the head size and his occipito-frontal head circumference (OFC) is two or morestandard deviations below the mean""A new epidemic of zika, chicungunya and dengue causes concern in Pernambuco doctors who leads the highestnumber of cases of microcephaly in the country, (https:. Wikipedia.org/wik/microcefalia en)Therefore, we conclude this study saying; the microcephaly, is not the result of a mosquito bite, and we can not considera small brain, but an unfinished brain, and that the epidemic has location and specific time, because the cells look with a certainprecision the place where it is being formed a brain Alfha- Delta, and GPS these cells are heredity them so this epidemic occurredespecially in Brazil, in the Northeast, specifically in Pernambuco.So it can be said that was born a JokeR-Delta child in this state, we can even identify the approximate time that the childwas born; April, May or June, since the recognition of this genius will happen much later, through science. They are very fewchildren who reach a high score in the HR (Human clock). That is a brain consists of eight brains coupled into one. Thus the reversecells do a scan for possession of this brain.